Measurement of γHV68 Infection in Mice - Pirooz, Sara Dolatshahi (MyJove Corporation, 2011)
γ-Herpesviruses (γ-HVs) are notable for their ability to establish latent infections of lymphoid cells(1). The narrow host range of human γ-HVs, such as EBV and KSHV, has severely hindered detailed pathogenic studies. Murine γ-herpesvirus 68 (γHV68) shares extensive genetic and biological similarities with human γ-HVs and is a natural pathogen of murid rodents(2). As such, evaluation of γHV68 infection of mice inbred strains at different stages of viral infection provides an important model for understanding viral lifecycle and pathogenesis during γ-HVs infection. Upon intranasal inoculation, γHV68 infection results in acute viremia in the lung that is later resolved into a latent infection of splenocytes and other cells, which may be reactivated throughout the life of the host(3,4). In this protocol, we will describe how to use the plaque assay to assess infectious virus titer in the lung homogenates on Vero cell monolayers at the early stage (5 - 7 days) of post-intranasal infection (dpi). While acute infection is largely cleared 2 - 3 weeks postinfection, a latent infection of γHV68 is established around 14 dpi and maintained later on in the spleen of the mice. Latent infection usually affects a very small population of cells in the infected tissues, whereby the virus stays dormant and shuts off most of its gene expression. Latently-infected splenocytes spontaneously reactivate virus upon explanting into tissue culture, which can be recapitulated by an infectious center (IC) assay to determine the viral latent load. To further estimate the amount of viral genome copies in the acutely and/or latently infected tissues, quantitative real-time PCR (qPCR) is used for its maximal sensitivity and accuracy. The combined analyses of the results of qPCR and plaque assay, and/or IC assay will reveal the spatiotemporal profiles of viral replication and infectivity in vivo.